Male partner approval on the use of modern contraceptive methods: factors determining usage among couples in Kibaha district, Tanzania - Judith Msovela; Anna Tengia-Kessy; Susan F. Rumisha; Daudi O. Simba; David P. Urassa; Gernard Msamanga (BMC, 2020)
Abstract Background Men in developing countries play an important role in the adoption of family planning (FP), either as actual users or supporters of their partners. Notwithstanding the universal knowledge on the contraceptive methods, their approval and use have been low among men in Tanzania. This study determined the magnitude and factors that influence men to use or approve the use of modern contraceptive methods with their spouses. Methods A cross sectional, community-based study was conducted in Kibaha, Pwani region in 2014. A total of 365 randomly selected married and cohabiting men; aged 18 to 60 years who had at least a child below the age of 5 years were interviewed using a structured questionnaire. Descriptive statistics were performed and associations between status of men using modern FP with their partners and potential factors were tested using Chi-square and Fisher's exact tests as appropriate. Logistic regression model was fitted to determine significant factors associated with male use of the methods with their partners. Results About 60 % of men (59.7%) reported to use modern FP methods. In the bivariate analysis, education level (odds ratio (OR) = 2.6, CI = 1.4-4.8; p = 0.002); men knowledge on any contraceptive method (OR = 24.1, CI = 7.3-79.9; p < 0.001); awareness of a nearby FP clinic (OR = 6.2, CI = 3.1-12.3; p < 0.001); number of children (OR = 2, CI = 1.1-3.6; p < 0.025) and presence of a provider during clinic visit (OR = 12.0, CI = 2.26-63.7; p < 0.004) were significantly associated with the use of FP. However, in the multivariable analysis, only knowledge on FP methods (adjusted odds ratios (AOR) =26.4; CI = 7.9-88.4, p < 0.001) and number of children a man had (AOR = 1.9; CI = 1.0-3.6, p = 0.039) remained significantly associated with the use of modern FP methods. Conclusion This study has shown that for men to use family planning methods with their partners, knowledge of FP methods and number of children are critical factors. Visiting a FP center alone or with a spouse, and availability of FP provider (during visit) also influence this practice. These findings emphasize a need to increase knowledge on contraception and family planning services access among men.